Pharmacokinetics of Doxycycline in Alpacas After Intravenous and Subcutaneous Administration - José Martínez; Pedro Marín; David A. Egas; Juan Llivi-Marcatoma; José Miguel Mira-Naranjo; Elena Badillo; María Teresa Yuste; Elisa Escudero; Juan Sebastián Galecio (Antibiotics)
Background/Objectives: Doxycycline, a tetracycline-class antibiotic, is commonly used across various species to treat infections caused by susceptible bacteria. However, pharmacokinetic data on its use in alpacas remains limited. This study aimed to investigate the pharmacokinetics of doxycycline following intravenous (IV) and subcutaneous (SC) administration in alpacas. Methods: A randomized crossover study (n = 6) was employed, with dosages of 5 mg/kg and 20 mg/kg after intravenous and subcutaneous administration, respectively. Blood samples were collected at predetermined times up to 96 h after both routes of administration. Plasma doxycycline concentrations were determined using validated high-performance liquid chromatography with a UV detector and then analyzed based on non-compartmental pharmacokinetic methods. Results: All alpacas maintained optimal health and general condition throughout the trial period. After intravenous administration, the Vz value (0.90 L/kg) indicated a good distribution of this antibiotic in the alpacas. The maximum concentration value (Cmax) after SC administration of doxycycline was 1.40 µg/mL, reached at 1.92 h. Low bioavailability (F = 36.83%) of doxycycline was observed after SC administration. Conclusions: PK/PD ratios calculated from the pharmacokinetic data obtained, at a dose of 20 mg/kg and SC route of administration, suggest that doxycycline administered every 24 h could be effective against bacterial infections with MICs of 0.125 and 0.5 µg/mL. However, multi-dose and pharmacodynamic studies are needed to further evaluate the efficacy of using doxycycline in alpacas.